SPIN-1/2 PARTICLES IN TORSION GRAVITY WHEN A CONSTANT ELECTRIC FIELD IS PRESENT - Keskin, Ali İhsan; Binbay, Fatma Figen; Açıkgöz, İrfan; Saltı, Mustafa (EDITURA ACAD ROMANE, 2013)
In this work, we focus on the dynamics of Dirac particles in the presence of a constant electric field in a cosmological anisotropic universe. Instead of Einstein's theory of general relativity, we perform the calculations using the teleparallel theory of gravity which is also called as the torsion gravity. First, we found the exact solution of the teleparallel Dirac equation in an anisotropic Bianchi-I universe. Second, the harmonic oscillator behaviour of the solution and then the quantization of oscillation frequency had been discussed. Third, we investigated the spin precession of Dirac particles and dispute the axial-vector spin coupling term.
Keywords: Dirac; Spin-1/2 particle; Torsion; Teleparallel gravity